A Heart Rate Monitoring and Notification System Using Arduino Platform - Alina-Maria MOCANU; Mihaela MARIN; Florin-Bogdan MARIN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
Heart rate measurements are widely used for various purposes that require an accurate and reliable method to measure it. The most common method used is by ECG, which is widely available and non-invasive. Another non-invasive, photoplethysmography (PPG) technology can also be used to measure blood pressure and oxygen saturation.